Chlamydia pneumoniae seroprevalence in immunocompetent and immunocompromised populations in Milan. Issue 12 (December 1993) - Blasi, F; Cosentini, R; Schoeller, M C; Lupo, A; Allegra, L
Abstract : BACKGROUND--Chlamydia pneumoniae is drawing increasing attention as an agent of respiratory tract infection. Specific antibody prevalence in western countries is low in preschool children and reaches more than 50% in adults. However, little is known about the prevalence of this infection in immunocompromised subjects such as HIV-I infected patients. The aim of this study was to evaluate the seroprevalence of Chl pneumoniae in immunocompetent and immunocompromised (HIV-1 infected) paediatric and adult populations. METHODS--Between March 1991 and September 1992 764 healthy subjects (421 men and 343 women, age range six months-81 years), 96 HIV-I infected (73 men and 23 women, age range 18-35 years) and 126 HIV-I negative intravenous drug users (92 men and 34 women, age range 18-37 years), and 50 children (23 boys and 27 girls, age range 8-123 months) with vertically transmitted HIV-I infection were studied. For each subject an HIV-I test (ELISA and Western blot) was performed, together with a microimmunofluorescence test for IgG and IgM antibodies to Chl pneumoniae specific antigen (TW-183). RESULTS--In the healthy population a low prevalence (11%) was observed in children under 10 years of age, which increased progressively to 58% in adults over 70 years. In the HIV-I infected population Chl pneumoniae seroprevalence was higher than in immunocompetent controls (children, 26% v 11%; drug users, 60% v 40%). Moreover, in drug users this difference was also observed in comparison with HIV-1 negative intravenous drug users (60% v 33%). CONCLUSIONS--Our data on Chl pneumoniae seroprevalence in a healthy population are consistent with those reported by others in western countries. Moreover, HIV-I infected subjects seem to be at higher risk of developing Chl pneumoniae infections.